Espiritualidade no trabalho: um estudo envolvendo servidores da Universidade Federal de Santa Maria - Moreira, Diogo Coelho (2021)
Profound changes occur in the world of work and, consequently, in people management, giving rise to issues such as spirituality within the organizational environment. Private companies immediately come to mind with regard to dealing with management in the organizational environment. However, it is necessary and punctual that the management of people in public organizations also accompanies these inevitable changes in the world of work. Therefore, this study aims to propose a model for measuring spirituality at work for the Brazilian Public Administration. The product of this research makes it possible to comprehend, through management, the spirituality in the work of the organization's employees. It is a first step in decision making regarding the implementation of policies and actions for the development of this construct. To this end, a quantitative and descriptive research was carried out, by means of a survey concerning the application of the model of spirituality in the workplace of Ashmos and Duchon (2000). The following dimensions were taken into account: sense of community, meaningful work and inner life. The model was applied to the Technical-Administrative Attendants in Education (TAEs) of the Federal University of Santa Maria. 366 TAEs participated in the research, which showed a positive perception of spirituality at work. The respondent's belief was the sociodemographic factor that influenced this perception the most. Afterwards, as a first step in the validation of the model to Public Administration, the dimensions were subjected to exploratory factor analysis, which resulted in the exclusion of variables from the dimensions of sense of community and inner life, in order to meet the statistical criteria. The validation was completed through confirmatory factor analysis, which assessed the fit and the construct validity of the model. The adjustment was optimized through the exclusion of one variable and the inclusion of a correlation between the two others. Both changes occured in the dimension work with meaning. The results obtained and the theoretical foundation raised inthis study, made it possible to propose an instrument for measuring spirituality at work, which is suitable for the Brazilian Public Administration.